2020
DOI: 10.1186/s12906-020-02970-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation and quantification of major biomarkers in ‘Mahasudarshan Churna’- an ayurvedic polyherbal formulation through high-performance thin-layer chromatography

Abstract: Background: Mahasudarshan Churna (MC) is a polyherbal Ayurvedic medicine that is employed in fever (especially chronic type), cold and malaria, improvement of digestion and appetite, removes toxins from the blood, boosts immunity and protects against common bacterial infections. Methods: Validation and quantification of oleanolic acid (OA), ursolic acid (UA), mangiferin (M), gallic acid (GA), quercetin (Q) and curcumin (C) in commercial MC formulations by HPTLC method. Mobile phase, hexane: ethyl acetate: acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The mobile phase was composed of 70% methanol (A) and 30% water (B) with a 0.8 mL/min eluent velocity, under a detection temperature of 30 °C. The UV detection wavelength of GA was set at 254 nm. The UV detection wavelength of Res was set at 306 nm. The content of GA was calculated according to the standard curve ( y = 18666 x – 67.804, R adj 2 = 0.9999). The content of Res was calculated according to the standard curve ( y = 71002 x + 65.388, R adj 2 = 0.9999).…”
Section: Methodssupporting
confidence: 82%
“…The mobile phase was composed of 70% methanol (A) and 30% water (B) with a 0.8 mL/min eluent velocity, under a detection temperature of 30 °C. The UV detection wavelength of GA was set at 254 nm. The UV detection wavelength of Res was set at 306 nm. The content of GA was calculated according to the standard curve ( y = 18666 x – 67.804, R adj 2 = 0.9999). The content of Res was calculated according to the standard curve ( y = 71002 x + 65.388, R adj 2 = 0.9999).…”
Section: Methodssupporting
confidence: 82%
“…The concentration of UA from lysates was estimated by HPTLC and densitometric analysis, after liquid/liquid extraction with ethyl acetate [ 25 , 26 ]. Fifty µL of sonicated bacteria (lysates) were added to 1 mL of ethylacetate.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies employing high-performance thin-layer chromatography (HPTLC) [15][16][17][18][19] and highperformance liquid chromatography (HPLC) [20][21][22][23] to estimate these markers alone or in combination have been published. However, a thorough review of the literature found that no validated HPTLC approach for simultaneously estimating all three markers has been published.…”
Section: Introductionmentioning
confidence: 99%